Ramsar Convention and the wise use of wetlands: rethinking inclusion - Joshi, Deepa; Gallant, Bryce; Hakhu, Arunima; de Silva, Sanjiv; McDougall, C.; Dubois, Mark; Arulingam, Indika (University of Wisconsin Press, 2021)
The Ramsar Convention on Wetlands emphasizes the “wise use” of wetlands by conserving the ecological character of wetlands while managing the socio-economic value these landscapes hold for different stakeholders. Reviewing the Convention obligations, resolutions, and guidelines through a feminist political ecology lens, we find them to be overtly simplistic and technocratic. A deliberately generic framing of socio-ecological interrelations and of economic trade-offs between wetland uses and users obscures broader political and social contexts which shape complex nature-society interrelations in the use, management, and governance of wetlands. Poverty, the cultural significance of wetlands—particularly for indigenous communities—and gender equality have only recently been considered in wetlands management and governance guidelines and interventions. These recent additions provide little insight on the power imbalances which shape plural values, meanings, experiences, and voices in wetlands use and governance, especially for the most marginalized of wetlands users. We welcome the call for a “reformulation” of a socio-ecological approach to managing and governing wetlands, but caution that unless wetlands governance structures and processes are re-politicized, changes in policies and approaches will likely remain rhetorical.